2013
DOI: 10.1038/psp.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ritonavir on 99mTechnetium–Mebrofenin Disposition in Humans: A Semi‐PBPK Modeling and In Vitro Approach to Predict Transporter‐Mediated DDIs

Abstract: A semiphysiologically based pharmacokinetic (semi-PBPK) model was developed to describe a unique blood, liver, and bile clinical data set for the hepatobiliary imaging agent 99mTechnetium–mebrofenin (99mTc–mebrofenin), and to simulate sites/mechanisms of a 99mTc–mebrofenin–ritonavir drug–drug interaction (DDI). The transport inhibitor ritonavir (multiple-dose: 2 × 300 mg) significantly increased systemic 99mTc–mebrofenin exposure as compared with control (4,464 ± 1,861 vs. 1,970 ± 311 nCi min/ml; mean ± SD), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 39 publications
3
53
2
Order By: Relevance
“…The role of metabolic clearance and transporter-enzyme interplay in complicating the prediction of intracellular concentrations in hepatocyte systems has been emphasized ( Parker and Houston, 2008;Brown et al, 2010). Hepatic intracellular C unbound , Kp u,u , and subcellular localization information has improved predictions and/or explained seemingly discrepant pharmacokinetic-pharmacodynamic relationships with a variety of endpoints involving efficacy (Dollery, 2013;Shitara et al, 2013), toxicity , and drug disposition, including transport (Kudo et al, 2007), metabolism (Obach, 1996(Obach, , 1999Deshmukh and Harsch, 2011), and related DDIs (Yamano et al, 1999;Chen et al, 2008;Sato et al, 2010;Pfeifer et al, 2013). Intracellular C unbound and subcellular localization of drugs are challenging to measure accurately, and our understanding of hepatocellular drug disposition remains rudimentary (Chu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The role of metabolic clearance and transporter-enzyme interplay in complicating the prediction of intracellular concentrations in hepatocyte systems has been emphasized ( Parker and Houston, 2008;Brown et al, 2010). Hepatic intracellular C unbound , Kp u,u , and subcellular localization information has improved predictions and/or explained seemingly discrepant pharmacokinetic-pharmacodynamic relationships with a variety of endpoints involving efficacy (Dollery, 2013;Shitara et al, 2013), toxicity , and drug disposition, including transport (Kudo et al, 2007), metabolism (Obach, 1996(Obach, , 1999Deshmukh and Harsch, 2011), and related DDIs (Yamano et al, 1999;Chen et al, 2008;Sato et al, 2010;Pfeifer et al, 2013). Intracellular C unbound and subcellular localization of drugs are challenging to measure accurately, and our understanding of hepatocellular drug disposition remains rudimentary (Chu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pfeifer et al (2013a) reported that using [I] u,cell of ritonavir correctly predicted no clinical MRP2-mediated DDI between ritonavir and 99m Tc-mebrofenin, whereas predictions based on [I] t,cell of ritonavir led to a false-positive prediction of DDI liability. In the case of telmisartan, simulations using [I] t,cell and [I] t,cyt slightly overpredicted TCA C t,Cells compared with simulations using [I] u,cell and [I] u,cyt .…”
Section: Discussionmentioning
confidence: 99%
“…However, the static method, based on the ratio of total plasma maximum concentration and IC 50 or inhibition constant (K i ) of the inhibitor, may not accurately predict the hepatic disposition of victim substrates. Limitations associated with the static method may explain the lack of cholestatic liability of some multidrug resistance-associated protein (MRP)2 and BSEP inhibitors (Dawson et al, 2012;Pfeifer et al, 2013a). To accurately translate transporter inhibition data (i.e., IC 50 or K i ) to the prediction of hepatocellular exposure of victim substrates, a number of factors should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, rifampicin administration blocks the rMRP2 and increases the hepatic accumulation of the SPECT tracer 99m Tc-mebrofenin (Neyt et al, 2013) and the PET tracers 11 C-telmisartan (Takashima et al, 2011) and [11C] TIC-Me (Kusuhara, 2013). Interaction of ritonavir with 99m Tc-mebrofenin was also recently investigated (Pfeifer et al, 2013). We demonstrated that rifampicin blocks BOPTA entry into normal livers (Daali et al, 2013).…”
Section: Modifications Of Transport Induced By Drug-drug Interactionsmentioning
confidence: 99%
“…In drug development, the prediction of transporter-mediated drug-drug interactions is crucial for drug efficacy and safety and the development of physiologically based pharmacokinetic (PBPK) models is important to estimate the concentrations of competing drugs at the sites of interaction (Pfeifer et al, 2013;Yoshida et al, 2013). Although several groups have succeeded in constructing PBPK models to predict hepatic concentration-time profiles, strategies to analyze transporter-mediated drug-drug interactions with these models are lacking (Watanabe et al, 2010;Jones et al, 2012;Rostami-Hodjegan, 2012;Pfeifer et al, 2013). Once these PBPK models are established, the effects of various competitions can be anticipated and quantitatively estimated.…”
Section: Modifications Of Transport Induced By Drug-drug Interactionsmentioning
confidence: 99%